Socialist Register 2008 Global Flashpoints / Reactions to Imperiaslism and Neoliberalism - Leys Colin; Panitch Leo (Savalas Publications, 2007)
This volume surveys the key flashpoints of Resistance today. The roots of Neoliberalism, Marxian and Keynesian Critiques of Neoliberalism, Neoliberalism and the Discounted, The Islamic Ethic and the Spirit of Turkish Capitalism Today, Islam and Islamists & West.